2012
DOI: 10.2169/internalmedicine.51.7992
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Autoimmune Pancreatitis Showing Narrowing of the Main Pancreatic Duct after Cessation of Steroid Therapy in the Clinical Course

Abstract: Autoimmune pancreatitis (AIP) is characterized by irregular narrowing of the main pancreatic duct (MPD), and narrowing of the MPD is an essential criterion for the diagnosis of focal/segmental AIP according to the Japanese diagnostic criteria 2011. We report a 55-year-old man in whom magnetic resonance imaging showed two masses in the pancreatic head and tail and whose pancreatogram was normal at first. However, the two masses changed into diffuse swelling of the pancreas, and diffuse narrowing of the MPD appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In this study, the authors did not mention the timing of recovery of biliary findings in their cases. Another report indicated that only 2 weeks of steroid treatment induced an improvement in the pancreatic morphology in a case with mass-forming IgG4-related autoimmune pancreatitis (10). In our case, after 10 days of corticosteroid treatment, CBD involvement was the first to disappear completely on MRI and it took a couple of months to see a similar complete response in the pancreatic parenchyma and MPD.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, the authors did not mention the timing of recovery of biliary findings in their cases. Another report indicated that only 2 weeks of steroid treatment induced an improvement in the pancreatic morphology in a case with mass-forming IgG4-related autoimmune pancreatitis (10). In our case, after 10 days of corticosteroid treatment, CBD involvement was the first to disappear completely on MRI and it took a couple of months to see a similar complete response in the pancreatic parenchyma and MPD.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, recent reports have demonstrated atypical cases that did not meet the criteria before or during the steroid therapy, but nevertheless fulfilled the condition of definitive AIP after steroid withdrawal with the development of narrowing of the main pancreatic duct [30] or hilar bile duct [21]. These phenomena suggested another necessity of careful follow-up after a course of steroids, after a negative work-up by EUS-FNAB [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, one case in this study showed no response by US and CT and required ERCP, which revealed an improvement in the narrowing of the MPD and the occurrence of hilar bile duct stenosis after the withdrawal of corticosteroid [33,48] . Similarly, some cases of AIP fulfill the diagnostic criteria after cessation of steroid [73] , so that clinicians need to remain aware of this. Many diagnostic criteria including those for ICDC (Table 2) can include evaluation of a steroid response either in the pancreatic or extrapancreatic lesions [9,17,18,25] , but the diagnosis is worrisome when the steroid response is seen only in the extrapancreatic lesions and not in the pancreas.…”
Section: Response To Steroidmentioning
confidence: 99%